Storytelling and Technology Combine to Create Student Engagement Around Locally Relevant Climate Change Topics. - Leckey, E.; Littrell-Baez, M.; Tayne, K.; Gold, A. U.; Okochi, C.; Oonk, D.; Smith, L. K.; Lynds, S. E. (American Geophysical Union, Fall Meeting 2017, 2017)
Storytelling is a powerful way for students to engage with science topics, particularly topics that may initially seem too broad to impact their lives, like climate change. Empowering students to telling a personal story about climate change's effects and helping them turn their story into a film is powerful approach. Especially because these films can be shared globally and gives students a voice around a complex topic like climate change. Here, we present impacts of the Lens on Climate Change program (LOCC), which engages middle and high school students in producing short films featuring how climate change impacts their communities. LOCC is offered as an intensive week-long summer program and as an extracurricular program during the school year. The majority of student participants are recruited from historically underserved communities and come from ethnical and socioeconomically diverse backgrounds. Survey data revealed that LOCC participants had a significant increase in their belief in the reality of climate change after participation in their program relative to students in a demographically-matched control groups. Furthermore, participant responses on reflection surveys given after the program included statements that suggest that students had begun thinking more deeply about climate change as a serious global challenge and felt empowered to take actions to mitigate climate change and/or spread awareness in their communities. The majority of students in the LOCC program also reported being very proud of their film and intended to share their film with their friends and family. Additionally, we explored the long-term impacts of participation by interviewing students a year after the program and offered them the opportunity to make a subsequent film. Students in this "advanced group" reported being more aware of climate change in their community following making their films and were enthusiastic to increase their filmmaking skills through producing additional films. We suggest that the combination of storytelling and filmmaking gives students a means to become part of the climate change narrative and to engage in thinking about and acting on climate change at a broader level than they might otherwise be comfortable doing.